Applications of chitosan in post-harvest fruit (Research, Society and Development, 2022)
Aiming to investigate solutions that improve the problems of processing and storing fruits after harvest, the present work carried out a bibliographical review about the use of chitosan in the postharvest quality of fruits, pointing out its main results in several researches. For this, inclusion criteria were used in the search in the databases of Portal de Periódicos from Capes, Scielo and Google Academic. The biopolymer is extracted from chitin, found mainly in crustacean shells and after the steps of deproteinization, demineralization, discoloration and deacetylation, and presents properties of biocompatibility, nontoxicity, versatility, adsorption, biodegradable, among others. Due to these, it is applied in several sectors, including agriculture, acting in plant production, as a biostimulant, inhibiting the growth of microorganisms and improving the growth, development and productivity of several plants. Also, it can be applied to fruits, due to the rapid deterioration that occurs as a result of reactions during its ripening, losing its quality as a result. Thus, 11 studies were surveyed that demonstrate that chitosan allows the preservation of different fruits through the formation of coverings around it, maintaining its physical and physicochemical characteristics, reducing infections, thus extending the shelf life and its period of ripening. In view of this, it has a positive performance in the agronomic field, in research with an emphasis on post-harvest, being a notable alternative to current techniques for the use of agrochemicals.